Understanding the Evolution of Entrepreneurial Learning: A Bibliometric Overview - Fadli Agus Triansyah; Hari Mulyadi; Endang Supardi; Baandaalr Lizein (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
This research aims to conduct a bibliometric analysis of "entrepreneurial learning." Using VosViewer software, we analyzed publication data related to this topic, including keywords, affiliation, country, and subject area, from a Scopus database containing 48 documents. The analysis results reveal that "entrepreneurial learning" is a topic that continues to grow in academic literature, focusing on the role of learning in the context of entrepreneurship. The United States dominates in the number of publications, but significant global contributions come from the United Kingdom, Canada, and other countries. Diverse subject areas, such as business management, social sciences, and economics, are involved in this research, reflecting a multidisciplinary approach to understanding this topic. In addition to the main keywords, such as "entrepreneurship" and "learning," several other interesting keywords, such as "cognition" and "curricula," were also identified. This analysis provides an in-depth look at the dynamics and diversity in entrepreneurship research and entrepreneurial learning, which can guide better entrepreneurship research and practice in the future.